Satisfaction by the certain subjective success in career - Janjić Ivana; Ilić Đurđijana (Trendovi u Poslovanju)
In order for an organization to successfully operate, it is necessary to know all employees and to establish an agreement between individual and organizational goals, which means that it should follow the following business philosophy: "Great performance and great satisfaction of the individual." However, what constitutes the basis of quality work organizations are reliable employees who are satisfied with their work, are ready to progress and learn and thus profit themselves and the organization either in material or otherwise. Employees who are not satisfied will not do the job properly, giving rise to direct pecuniary damage. In addition, dissatisfied employees will want to leave the job, in which case all resources previously invested in that employee will be practically thrown into the water. For modern business, characterized by strong competition and constant change, the labor market dictates the requirements of developing personal abilities. That is why career development has become a key responsibility of individuals themselves who develop their personal abilities to actively maintain their own employability in a changing labor market. In order for the organization to function and profit profitably, it is necessary to control and improve the satisfaction of employees, because the success of each organization rests on satisfactory human resources.